Administration of Drugs/Gene Products to the Respiratory System: A Historical Perspective of the Use of Inert Liquids - Alapati, Deepthi; Shaffer, Thomas H. (Frontiers in Physiology, 2022)
The present review is a historical perspective of methodology and applications using inert liquids for respiratory support and as a vehicle to deliver biological agents to the respiratory system. As such, the background of using oxygenated inert liquids (considered a drug when used in the lungs) opposed to an oxygen-nitrogen gas mixture for respiratory support is presented. The properties of these inert liquids and the mechanisms of gas exchange and lung function alterations using this technology are described. In addition, published preclinical and clinical trial results are discussed with respect to treatment modalities for respiratory diseases. Finally, this forward-looking review provides a comprehensive overview of potential methods for administration of drugs/gene products to the respiratory system and potential biomedical applications.